Bacterial skin infections. Issue 8 (August 2019) - Gleeson, David
Every year, around 24% of the population consults their GP about a skin problem. Bacterial skin infections, especially in the paediatric and elderly populations, are common and some are potentially life-threatening. The most common bacterial pathogens associated with skin infections are Staphylococcus aureus and Staphylococcus pyogenes . This article will cover diagnosis and management of the most common skin infections, high-lighting important features of potentially lethal presentations requiring hospitalisation. Infections affecting superficial layers of the skin, deeper layers, and accessory tissues are considered.